Kristjánsson, K. & Flowers, B. J. (2023). Phronesis: Retrieving Practical Wisdom in Psychology, Philosophy, and Education. OUP Oxford. 352 pp. - de la Peña Barroso, Ana (UNIR, 2026)
Reseña
Keywords: reseña